PEMELIHARAAN HUBUNGAN PERTEMANAN ANTARA PEMAIN GAME ONLINE VALORANT DALAM KOMUNITAS VIRTUAL - Nadif Rizqulloh, Muhammad; Rahardjo, Turnomo; Qurrota Ayun, Primada (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The virtual space formed by online game players has both sides, positive and negative. One of the negative impacts is the space for conflict to arise between members. Many conflicts between members start with activities such as chatting and joking, creating sensitivity among members. The messages sent are often considered as hatred (hate speech). Cyberspace causes interactions between individuals to be influenced by the media, making it impossible to know the psychological situation of the other side. This causes an imbalance in social relations in cyberspace. This research aims to determine the maintenance of friendship relationships that take place in the virtual community of Valorant game players without having to meet and find out the individuals who are members of the virtual community in maintaining friendships by managing conflicts that arise.The theory used is the maintenance of friendship relationships, symbolic interactionism theory and relational dialectics theory and uses phenomenological research methods. The results obtained in this research are that maintaining a friendship within a virtual community is not easy and dynamic. Maintenance for the friendship to adapt depends on the individual conditions and not tied to a fixed flow. Furthermore, maintaining a friendship has many factors in it, starting from the form of communication, communication media, commitment formed, handling conflict, and the distance that separates them. Commitment is a major factor in maintaining a longdistance friendship and communication is a crucial aspect in maintaining relationships. Individuals who are members of virtual communities try to be open with each other.